A specific sphingosine kinase 1 inhibitor attenuates airway hyperresponsiveness and inflammation in a mast cell-dependent mouse model of allergic asthma - Price, Megan M. (2013)
Background: Sphingosine-1-phosphate (S1P), which is produced by 2 sphingosine kinase (SphK) isoenzymes, SphK1 and SphK2, has been implicated in IgE-mediated mast cell responses. However, studies of allergic inflammation in isotype-specific SphK knockout mice have not clarified their contribution, and the role that S1P plays in vivo in a mast cells and IgE-dependent murine model of allergic asthma has not yet been examined. Objective: We used an isoenzyme-specific SphK1 inhibitor,SK1-I, to investigate the contributions of S1P and SphK1 to mast cell-dependent airway hyperresponsiveness (AHR) and airway inflammation in mice. Methods: Allergic airway inflammation and AHR were examined in a mast cell-dependent murine model of ovalbumin (OVA)-induced asthma. C57BL/6 mice received intranasal delivery of SK1-I before sensitization and challenge with OVA or only before challenge. Results: SK1-I inhibited antigen-dependent activation of human and murine mast cells and suppressed activation of nuclear factor-kB (NF-kB), a master transcription factor that regulates the expression of proinflammatory cytokines. SK1-I treatment of mice sensitized to OVA in the absence of adjuvant, in which mast cell-dependent allergic inflammation develops, significantly reduced OVA-induced AHR to methacholine; decreased numbers of eosinophils and levels of the cytokines IL-4, IL-5, IL-6, IL-13,IFN-g, and TNF-a and the chemokines eotaxin and CCL2 in bronchoalveolar lavage fluid; and decreased pulmonary inflammation, as well as activation of NF-kB in the lungs.